KESIAPAN KONTRAKTOR TERHADAP KEBIJAKAN PRESERVASI JALAN NASIONAL DI SUMATERA SELATAN - Budilukito, Andri; Mulyono, Agus Taufik (Jurnal HPJI, 2016)
AbstractÂ Directorate General of Highways, through the Directorate of Roads Preservation, will apply a new policy, namely long segment national road preservation, to maintain national roads. Long segment road preservation is expected to change the paradigm of the contractors, from the road construction executors to become road managers. This purpose of this study is to evaluate the readiness of the contractors on the long segment road preservation policy. The sample for this study consists of 109 respondents, including 63 respondents from the roads manager, 21 respondents from the supervising consultants and 25 respondents from the contractors. The method used in this study is the structural equation modeling method, supported by AMOS ver. 21. The results show that the causal relationship between the variables of contractorâs performance with quality performance of long segment road preservation amounted to 31.20%. The causal relationship between the variables of contractorâs performance to each variables, such as human resources, materials, equipment, methods, and quality control contribute significantly by 41.80%, 78.80%, 26.10%, 73.20%, and 42.20%, respectively. Keywords: contractorsâ performance, long segment road preservation, structural equation modelingÂ Â AbstractÂ Direktorat Jenderal Bina Marga, melalui Direktorat Jalan Preservasi, akan menerapkan kebijakan baru, yaitu long segment untuk preservasi dan pemeliharaan jalan nasional Indonesia. Long segment untuk preservasi jalan nasional diharapkan mengubah paradigma kontraktor, dari yang hanya sebagai pelaksana kegiatan konstruksi menjadi manajer jalan. Penelitian ini bertujuan untuk mengevaluasi kesiapan kontraktor pada preservasi jalan nasional long segment. Ukuran sampel pada penelitian ini adalah 109 responden, terdiri dari 63 responden dari manajer jalan, 21 responden dari konsultan pengawas, dan 25 responden dari kontraktor. Penelitian ini menggunakan metode struktural equation modeling dan didukung oleh AMOS ver. 21. Hasil yang didapat menunjukkan bahwa hubungan sebab akibat antara variabel kinerja kontraktor dengan kinerja kualitas long segment untuk preservasi jalan sebesar 31,20%. Hubungan sebab akibat antara variabel kinerja kontraktor untuk setiap variabel, seperti sumber daya manusia, material, peralatan, metode, dan kontrol kualitas masing-masing memberikan kontribusi sebesar 41,80%, 78,80%, 26,10%, 73,20%, dan 42,20%. Kata-kata kunci: kinerja kontraktor, preservasi jalan long segment, structural equation modeling